Are We Overdiagnosing Acute Kidney Injury in Pediatric Patients Following Cardiac Surgery?. (October 2015) - Soni, Meshal; Piggott, Kurt D.; DeCampli, William; Ramirez, Jorge; Pourmoghadam, Kamal; Fakioglu, Harun; Blanco, Carlos
Background: The use of two diagnostic criteria in the current literature has led to some degree of ambiguity in the precise diagnosis of acute kidney injury in pediatric patients undergoing surgery for congenital heart disease. This study aims to determine which criteria is the most accurate diagnostic indicator of acute kidney injury and determine whether the incidence is being overestimated based on the current criteria. Methods: This retrospective study consisted of 389 patients with congenital heart disease from birth to 18 years, who underwent cardiac surgery. The statistical tests conducted were the student t test and chi-square test. Outcomes measured included hospital length of stay, duration of mechanical ventilation, and mortality. Results: The incidence rate of acute kidney injury diagnosed by the pediatric Risk, Injury, Failure, Loss, and End-Stage Renal Disease (RIFLE) criterion was 56% compared to 24.4% for the Acute Kidney Injury Network criterion. The pediatric RIFLE criterion consists of the following subsets: risk, injury, failure, loss, and end-stage renal disease. Patients classified in the "risk" subset of the pediatric RIFLE criterion who failed to meet Acute Kidney Injury Network criterion were compared to patients without acute kidney injury. Comparison of intensive care unit outcomes between these groups lacked statistical significance for all variables except the duration of mechanical ventilation postoperatively. Conclusion: Although recent research in this field identified the pediatric RIFLE criterion as the most sensitive indicator of acute kidney injury, the results of this study suggest the pediatric RIFLE criterion overestimates acute kidney injury incidence and that the Acute Kidney Injury Network criterion is the more accurate diagnostic indicator.